Temperature-induced variations in dulse (Devaleraea mollis) nutrition provide indirect benefits on juvenile red abalone (Haliotis rufescens) Growth - Rizzo, Natalie R.; Beckert, Samantha B.; Boles, Sara E.; Gross, Jackson A. (Frontiers in Marine Science, 2024)
Changes in climate conditions can have cascading repercussions for organismal performance and survival, altering the productivity of aquatic systems. While numerous studies have examined the direct effects of temperature on species fitness, fewer studies have analyzed how individual impacts may translate to downstream primary consumers. Temperature-induced changes in the nutritional quality of seaweed may cause critical shifts in energy and nutrient availability for these consumers. A multifaceted experiment was conducted to assess the indirect impacts of California’s coastal climate conditions on abalone growth. This experiment fed juvenile red abalone (Haliotis rufescens) of two different size classes in ambient water conditions with the seaweed dulse (Devaleraea mollis), conditioned at 13°C, 15°C, and 17°C for 92 days. Nutritional analyses revealed significantly higher protein and nitrogen content in the 17°C dulse culture than in the 15°C and 13°C cultures, and no significant differences in carbohydrates. Furthermore, analyses on body weight ratio and condition factor indicate that juvenile red abalone of smaller size display significantly better growth and condition when fed dulse cultured at higher temperatures. Differences between size classes suggest that temperature changes, and subsequent shifts in the nutritional composition of dulse, may have greater impacts on smaller, younger red abalone.